An Examination of Non-Pathologist Physicians' Experiences with and Perceptions of the Autopsy. (28th October 2021) - Hagen, E S; Mirza, K M; Anderson, E; Cox, B
Abstract: Introduction/Objective: The autopsy is an undervalued and underutilized resource in medicine. Many people believe autopsies are used solely in forensics while in fact much of what we know about human disease comes from examining the human body at autopsy. The decrease in requests for autopsy over the past several decades possibly results from medical professionals' lack of exposure to and understanding of autopsy. We conducted a survey to explore non-pathologist physicians' exposure to and understanding of the autopsy and discover challenges and barriers faced by non-pathologists when requesting an autopsy. Better understanding of non-pathologist physicians' views and experiences can guide further inquiry or intervention to remove barriers to autopsy requests. Methods/Case Report: We disseminated a Google Forms survey via Twitter, tweeting weekly between 10/26/20- 2/26/2021 to obtain a convenience sample. Mean differences in continuous variables were assessed using an independent samples T-test. Chi-squared analyses were employed to report proportional differences in categorical variables. Where appropriate, comparisons of Likert scores (percentages) were performed using ordinal regression methods and reported as odds ratios. Analyses were performed on SPSS statistical software (v.27). P-value was considered significant if <0.05. Results (if a Case Study enter NA): 162 physicians responded to the survey. 29 responses were excluded (work outside US, practice pathology, or in residency), resulting in 133 surveys for analysis. Preliminary analysis suggests that Likert scores were generally favorable (>3) for questions that asked whether the autopsy was of benefit to the clinical team, public health, and family closure. Also, Likert scores revealed that physicians experience barriers surrounding the autopsy in terms of understanding and comfort with tasks related to the autopsy. Conclusion: Our study reveals that physicians are often unsure about the cause of their patients' death, highlighting the continued importance of the autopsy in patient care. Barriers to autopsy use may include limited understanding of the procedure, how it is financed, and how to request an autopsy. Physicians also express discomfort with discussing autopsy with families. Education and specific training on conversations about the autopsy may increase use.